Pengaruh Kualitas Produk dan Brand Image Terhadap Keputusan Pembelian The Originote Medan - Hutabarat, Eka Risliza Br; Adlina, Hafiza; Siregar, Onan Marakali (PT Alahyan Publisher Sukabumi, 2026)
Consumer purchasing decisions for skincare products are increasingly influenced by product quality and brand image, especially amidst the intense competition in the local cosmetics industry, such as The Originote in Medan. Reliable product quality and a positive brand image can increase consumer confidence in making purchases. This study aims to analyze the influence of product quality and brand image on purchasing decisions for The Originote products in Medan. This study uses a quantitative approach with an associative method and a non-probability sampling technique in the form of quota sampling with a total of 100 respondents. Primary data were obtained from questionnaires, while secondary data were obtained from literature studies. Analysis techniques include research instrument testing, classical assumption testing, multiple linear regression, and t-tests and F-tests. The results of the study indicate that partially, product quality has a positive and significant effect on purchasing decisions. Brand image is also proven to have a positive and significant effect on purchasing decisions. In addition, simultaneously, product quality and brand image have a significant effect on purchasing decisions for The Originote products in Medan. The Adjusted R Square value of 92.8% indicates that product quality and brand image variables contribute 92.8% to purchasing decisions, while the remaining 7.2% is influenced by factors outside this study.